2014
DOI: 10.3748/wjg.v20.i23.7466
|View full text |Cite
|
Sign up to set email alerts
|

Association ofMYO9Bgene polymorphisms with inflammatory bowel disease in Chinese Han population

Abstract: MYO9B gene polymorphisms may influence the sub-phenotypic expression of CD in China. No association between these MYO9B polymorphisms and intestinal permeability in IBD patients was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Five SNPs within MY09B gene were investigated, including rs1545620, rs962917, rs1457092, rs2305764 and rs2305767. Genotype distributions of the controls about rs1545620 in one study [ 17 ] did not conform to HWE [ 17 ] ( P = 0.002). The NOS scores of all included studies ranged from 5 to 7 stars, which suggested they were studies of high methodological quality.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five SNPs within MY09B gene were investigated, including rs1545620, rs962917, rs1457092, rs2305764 and rs2305767. Genotype distributions of the controls about rs1545620 in one study [ 17 ] did not conform to HWE [ 17 ] ( P = 0.002). The NOS scores of all included studies ranged from 5 to 7 stars, which suggested they were studies of high methodological quality.…”
Section: Resultsmentioning
confidence: 99%
“…The NOS scores of all included studies ranged from 5 to 7 stars, which suggested they were studies of high methodological quality. Six papers were carried out in Caucasian populations [ 14 - 16 , 18 , 20 , 21 ], and two in Asian populations [ 17 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations